A Novel Mutation in TSC2 Gene: A 34-Year-Old Female with Pulmonary Lymphangioleiomyomatosis with Concomitant Hepatic Lesions - Mehdi Nadiri; Mortaza Raeisi; Seyed Ali Mousavi Aghdas (Case Reports in Pulmonology)
Tuberous sclerosis complex (TSC) is an autosomal dominant disease resulting from mutation(s) in TSC1 or TSC2 genes. TSC is associated with the formation of hamartomas in the brain, heart, eyes, skin, kidneys, and lymphangioleiomyomatosis (LAM) of the lungs. LAM is almost restricted to women in reproductive age. Different mutations in TSC1 and TSC2 genes have been reported in the literature. Here, we present a female patient with TSC-LAM with a novel mutation in TSC2 gene. The patient also had multiple hepatic angiomyolipomas, which is a relatively less-reported manifestation of the disease. The impact of this mutation on the pattern of disease presentation and response to treatment is not clear yet.